UPAYA MENINGKATKAN HASIL BELAJAR SISTEM KELISTRIKAN OTOMOTIF DI SMK NEGERI 1 PADANG - Raffles Raffles (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2016)
The main purpose of this study, researchers are as motivation for teachers in order to implement contextual learning approach and encourage students' interest because it uses a learning model that is attractive. Contextual learning approach used in an effort to increase the students' learning outcomes. To see successes in the use of learning research methods class action. Of the learning process in the research that has been done, the CTL method can improve student learning outcomes automotive electrical system training eye.